2010
DOI: 10.1097/tp.0b013e3181c425fd
|View full text |Cite
|
Sign up to set email alerts
|

rHuEPo Reduces Ischemia-Reperfusion Injury and Improves Survival After Transplantation of Fatty Livers in Rats

Abstract: Erythropoietin improves marginal graft function and recipient survival after transplantation of fatty livers in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Twenty-six of included 40 articles are observational studies [14,, while the remaining are interventional studies [7,8,[15][16][17][18][43][44][45][46][47][48][49][50][51]. Nine in vitro cell culture studies were reported using various cell lines.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-six of included 40 articles are observational studies [14,, while the remaining are interventional studies [7,8,[15][16][17][18][43][44][45][46][47][48][49][50][51]. Nine in vitro cell culture studies were reported using various cell lines.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The 31 included animal studies score ranging from 2 to 6 (see Table 2), and contained 4 studies ranked A [18,19,45,50], 23 ranked B [15][16][17]23,24,27,28,[30][31][32][33][34][35][36][37][38]43,44,[46][47][48][49]51], and 4 ranked C [26,29,39,42]. In subject classification, the study of intervention gets the highest marks, owing to better control of temperature and blinded assessment of outcome.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,10 In stark contrast to our findings, hypoxia has been viewed by most as detrimental to liver regeneration, 28 and abrogating hypoxia through surgical maneuvers, like portal vein arterialization, has been considered beneficial to the regenerating liver. 25 Recently, investigators described the presence of the master regulator of hypoxia HIF-1a in regenerating livers after resection, 29,30 not just in response to hypoxic injury but as an important regulator of hepatic metabolism in general. 31,32 It also has been demonstrated that liver regeneration is actually increased in mice deficient for PHD-1 and that increased HIF-1a activity in the regenerating liver not only induced a protective response, but also accelerated liver regeneration.…”
Section: Article In Pressmentioning
confidence: 99%